PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM TIM PADA KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Diah Setyowati; Asri Laksmi Riani (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
This research aimed to analyze the effect of  transformational leadership on comittment  organizational; the effect transformational leadership on job satisfaction; team climate on job satisfaction and the effect of job satisfaction on comittment organizational.  The sample of research was the employees in PT. Bank Rakyat Indonesia (Persero) of Sukoharjo  consisting of 200 respondents. The method of sampling used was non probability sampling method and  quota sampling. Meanwhile the method of analyzing data used was Structural Equation Model (SEM).The result of hypothesis testing showed that transformational leadership affected negative and did not significantly on comittment organizational; transformational leadership affected significantly and positively the job satisfaction; team climate affected significantly and positively the job satisfaction; the job satisfation affected positively and significantly on comittment organizational and significantly mediated the effect transformational leadership and team climate on comittment organizational.